A relação entre satisfação na atividade sexual e qualidade de vida em pessoas idosas - Rodrigues, Carolina Freitas do Carmo (2019)
Objectives: To analyze the relationship between satisfaction in sexual activity and quality of life in the elderly Method: The method of the dissertation was divided into two stages. The first refers to a cross-sectional, population-based study, part of the SABE (Health, Welfare and Aging) Study, carried out in São Paulo city with elderly people (≥60 years) in 2010. To verify the association between categorical variables, Chi-square test with Rao & Scott correction, and the means by means of the Wald Test were used. The second stage was the elaboration of an educational booklet on sexual orientation for the elderly, based on an integrative review using the descriptors - elderly, sexual behavior, sexuality, sexually transmitted diseases - between the years 2007 and 2017. Results: The As for sexual satisfaction, 45.1% of the elderly reported being inactive satisfied and 37.0% satisfied, with 37.4% with monthly frequency of the activity. The physical component of quality of life was associated with sexual satisfaction for both men and women, and the highest averages of this component were found among satisfied elderly people. Considerations: Sexually satisfied active elderly individuals presented higher mean quality of life scores, evidencing the need to strengthen the health care network of the elderly regarding sex education, promoting openness to discuss the issue in society.